Widespread yet hidden in darkness: new troglobitic Hyalella species from Brazilian caves (Amphipoda: Hyalellidae) - Cardoso, Giovanna Monticelli; Oliveira, Marcus Paulo Alves De; Ferreira, Rodrigo Lopes (Zootaxa, 2025)
New species of the freshwater amphipod genus Hyalella have been discovered in groundwater habitats across Brazil. Hyalella amazonica sp. nov. and Hyalella karaja sp. nov. were collected from ferruginous caves in the state of Pará, while Hyalella nebula sp. nov. was recorded from ferruginous caves in the state of Minas Gerais. Hyalella uva sp. nov. was identified in a carbonate cave in the state of Rio Grande do Sul. The discovery of Hyalella species in Pará is particularly significant, as it constitutes the first documented occurrence of the genus within the Amazon biome. All newly described species are considered stygobionts, restricted to the caves where they were found. They exhibit troglomorphic traits commonly associated with subterranean adaptation, including body depigmentation and elongation of appendages, most notably antenna 1, which is markedly longer than antenna 2.